Peculiarities of teaching junior schoolchildren foreign-language oral speech - Кopzhassarova, U.I.; Аntontseva, Е.V. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article deals with the peculiarities of teaching junior schoolchildren foreign-language oral speech. The work also raises the problem of the necessity of teaching foreign languages at an elementary school. Authors explored peculiarities of psychological and physiological development of children of younger school age, studied and analyzed the works of psychologists and methodologists on a research problem, on the basis of which conclusions are made about necessity of a foreign language teaching at an early age, assuming acquaintance with the peculiarities of culture of the people of the country of the studied language. In the conclusion authors offered some recommendations about specificity of teaching junior schoolchildren oral speech at English lessons.
Бастауыш сынып оқушылардың шетел тілде сөйлей білу біліктілігіне үйретудің ерекшеліктері
Особенности обучения младших школьников иноязычной устной речи
Keywords: oral foreign-language speech; early training; lexical and grammatical skills; junior schoolchildren; monological and dialogical communication; younger school age; psychological and physiological peculiarities; pronunciation skills; lexical material; speech and situational exercises